Identifying facilitators and barriers for adolescents participating in a school-based HIIT intervention: the eXercise for asthma with commando Joe’s® (X4ACJ) programme - Melitta McNarry (BMC Public Health, 2020)
BackgroundHigh-intensity interval training (HIIT) elicits numerous health benefits, but little evidence is available regarding the feasibility of delivering school-based HIIT interventions. The aim of this study was to explore adolescents’ perceptions of a 6-month, 3 × 30-min sessions per week, HIIT intervention delivered either before or after school.MethodEighty adolescents allocated to the intervention group (13.3 ± 1.0 years; 45 boys) were invited to take part in semi-structured focus groups post-intervention. Participants were categorised as attendees (≥40% attendance) or non-attendees (< 5% attendance). Data were transcribed verbatim and thematically analysed deductively, with key emergent themes represented using pen profiles.ResultsResults showed that a school-based HIIT intervention can be an enjoyable form of exercise. Irrespective of attendance, similar facilitators and barriers to participating were highlighted, including benefits of participation, content of the exercise session and the intervention instructor.ConclusionThis study provides support for the delivery of a HIIT intervention in a school setting but highlights the importance of a flexible design and delivery to accommodate competing interests. There is a need to educate adolescents on the possible benefits of participation and to make the sessions enjoyable in order to increase their extrinsic and intrinsic motivation to sustain participation.